Impact of KChIP2 on cardiac electrophysiology and the progression of heart failure - Grubb, Soeren; Calloe, Kirstine; Thomsen, Morten B. (Frontiers in Physiology, 2012)
Electrophysiological remodeling of cardiac potassium ion channels is important in the progression of heart failure. A reduction of the transient outward potassium current (Ito) in mammalian heart failure is consistent with a reduced expression of potassium channel interacting protein 2 (KChIP2, a KV4 subunit). Approaches have been made to investigate the role of KChIP2 in shaping cardiac Ito, including the use of transgenic KChIP2 deficient mice and viral over-expression of KChIP2. The interplay between Ito and myocardial calcium handling is pivotal in the development of heart failure, and is further strengthened by the dual role of KChIP2 as a functional subunit on both KV4 and CaV1.2. Moreover, the potential arrhythmogenic consequence of reduced Ito may contribute to the high relative incidence of sudden death in the early phases of human heart failure. With this review, we offer an overview of the insights into the physiological and pathological roles of KChIP2 and we discuss the limitations of translating the molecular basis of electrophysiological remodeling from animal models of heart failure to the clinical setting.